On the spider genus Weintrauboa (Araneae, Pimoidae), with a description of a new species from China and comments on its phylogenetic relationships - Hormiga, Gustavo (Zootaxa, 2008)
Weintrauboa yele new species (Pimoidae) is described and illustrated based on specimens collected in China. The taxonomic status and distribution of Weintrauboa insularis (Saito, 1935) new combination and of W. chikunii (Oi, 1979) are discussed and the former species is illustrated based on specimens from the Sakhalin islands. Parsimony analysis of morphological characters provides support for the monophyly of Weintrauboa and for its sister group relationship to the genus Putaoa Hormiga and Tu, 2008. Some comments on the phylogenetic placement of the recently erected family “Sinopimoidae” are provided.